Inequalities within couples: Market incomes and the role of taxes and benefits in Europe - Francesco Figari; Herwig Immervoll; Horacio Levy; Holly Sutherland (University of Essex, Institute for Social and Economic Research (ISER), 2007)
In spite of there being few elements of tax or cash benefit systems in developed countries that are any longer explicitly gender-biased in a discriminatory sense, it is well recognised that they have significant gender effects. To the extent that women earn less than men on average under tax-benefit systems that are progressive, there is some redistribution from men to women overall. However, an aggregate perspective is insufficient for understanding how earning opportunities and public policies affect living arrangements at the family level in general and the circumstances of men and women in particular. Arguably, it is within the household that a gendered division of labour is most relevant. It is difficult to observe how income and other resources get allocated within households. We can, however, observe the incomes brought into the household and to what extent taxes and benefits mitigate (or indeed exacerbate) any inequality of income between men and women. We explore the effects of tax and benefit systems on differences in income and in incentives to earn income between men and women within couples in a selection of the member countries of the European Union (EU) using EUROMOD, the EU tax-benefit microsimulation model. This comparative perspective allows us to establish the relative effects of different policy regimes, given the underlying characteristics of each national population, using a consistent approach and set of incidence assumptions across countries.
Keywords: D31; H31; 330; within-household inequality; tax-benefit systems; Europe; gender; Haushaltseinkommen; Einkommensverteilung; Ehe; Familienbesteuerung; Simulation; EU-Staaten